Translation of the Word “Bagus” in Folklore Asal Mula Kata Babah Using Google Translate - Rafika Zahra (International Journal of English and Applied Linguistics (IJEAL), 2023)
Translating cultural terms is a study that should be explored further, particularly in translating cultural words using machine translation. Google Translate is a machine translation that was widely used by people to translate one language into another language. This study only focused on the cultural word "bagus" as the source data, and it was translated using machine translation, namely Google Translate from Indonesian to English. This study aimed to examine how Google Translate as a machine translation rendering the cultural word "bagus" in the folklore "Asal Mula Kata Babah" from Indonesian to English and also to find the appropriate translation strategy for translating the word "bagus" as a cultural word from Indonesian to English by using Google Translate. This study used the descriptive-qualitative method. In addition, this study used Newmark (1988) procedures of translation and Suryawinata & Hariyanto (2016) theory of contextual meaning. The result found that there were 8 data consisting of the word "bagus" and later it was translated using Google Translate. The result of this study also discovered that Google Translate accurately translated one data, and likewise with the contextual meaning. Also, the other data were not translated accurately and did not follow the contextual meaning. Moreover, this study obtained only two translation strategies: literal translation with 7 data and cultural equivalents with 1 data.